2020
DOI: 10.1002/cmdc.202000558
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecule Inhibition of the uPAR ⋅ uPA Interaction by Conformational Selection

Abstract: The urokinase receptor (uPAR) is a cell surface receptor that binds to the serine protease urokinase‐type plasminogen activator (uPA) with high affinity. This interaction is beneficial for extravascular fibrin clearance, but it has also been associated with a broad range of pathological conditions including cancer, atherosclerosis, and kidney disease. Here, starting with a small molecule that we previously discovered by virtual screening and cheminformatics analysis, we design and synthesize several derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(180 reference statements)
1
8
0
Order By: Relevance
“…Human and mouse uPA1-48 (huPA1-48 and muPA1-48), human and murine uPA1-48 fusion proteins (huPA1-48Ig and muPA1-48Ig) [ 120 ], and human and mouse pegylated uPA1-48 (PEGh1-48 and PEGhm1-48) [ 121 ] also inhibit tumour growth by inhibiting tumour stromal cell uPAR-dependent plasminogen activation. The small-molecule inhibitors IPR-456 [ 122 ], IPR-803 [ 123 ], IPR-3011 [ 124 ], IPR-3577 [ 125 ], 7 [ 126 ], LLL-1fsi [ 127 ], MS#479 [2-(pyridin-2-ylamino)-quinolin-8-ol] and MS#305 [2,2′-(methylimino)di (8-quinolinol)] [ 128 ], Compounds 6 and 37 [ 129 ], and docosahexaenoic acid (DHA) [ 130 ] inhibit the uPAR/uPA, uPAR/integrin, uPAR/Vn or uPAR/FPR interaction. The ligand-targeted toxins DTAT [diphtheria toxin (DT) and ATF] [ 131 , 132 ], DTATEGF (ATF, EGF and DT) [ 133 ], DTAT13 [ATF, interleukin-13 (IL-13) and DT] [ 134 , 135 ], eBAT (EGFATFKDEL 7mut) [ 136 141 ], ATF-SAP (ATF and Saporin) [ 142 , 143 ], PAI-2- N -AIE conjugate [5,7-dibromo- N -( p -hydroxymethylbenzyl)isatin and PAI-2] [ 144 ], DTU2GMCSF [DT and granulocyte–macrophage colony-stimulating factor (GM-CSF)] [ 145 ], ATF-PE38 and ATF-PE38KDEL [ATF and Pseudomonas exotoxin A (PE38)] [ 146 ] exert antitumor effects by targeting uPAR and releasing toxins.…”
Section: Targeting Upar For Antitumour Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Human and mouse uPA1-48 (huPA1-48 and muPA1-48), human and murine uPA1-48 fusion proteins (huPA1-48Ig and muPA1-48Ig) [ 120 ], and human and mouse pegylated uPA1-48 (PEGh1-48 and PEGhm1-48) [ 121 ] also inhibit tumour growth by inhibiting tumour stromal cell uPAR-dependent plasminogen activation. The small-molecule inhibitors IPR-456 [ 122 ], IPR-803 [ 123 ], IPR-3011 [ 124 ], IPR-3577 [ 125 ], 7 [ 126 ], LLL-1fsi [ 127 ], MS#479 [2-(pyridin-2-ylamino)-quinolin-8-ol] and MS#305 [2,2′-(methylimino)di (8-quinolinol)] [ 128 ], Compounds 6 and 37 [ 129 ], and docosahexaenoic acid (DHA) [ 130 ] inhibit the uPAR/uPA, uPAR/integrin, uPAR/Vn or uPAR/FPR interaction. The ligand-targeted toxins DTAT [diphtheria toxin (DT) and ATF] [ 131 , 132 ], DTATEGF (ATF, EGF and DT) [ 133 ], DTAT13 [ATF, interleukin-13 (IL-13) and DT] [ 134 , 135 ], eBAT (EGFATFKDEL 7mut) [ 136 141 ], ATF-SAP (ATF and Saporin) [ 142 , 143 ], PAI-2- N -AIE conjugate [5,7-dibromo- N -( p -hydroxymethylbenzyl)isatin and PAI-2] [ 144 ], DTU2GMCSF [DT and granulocyte–macrophage colony-stimulating factor (GM-CSF)] [ 145 ], ATF-PE38 and ATF-PE38KDEL [ATF and Pseudomonas exotoxin A (PE38)] [ 146 ] exert antitumor effects by targeting uPAR and releasing toxins.…”
Section: Targeting Upar For Antitumour Therapymentioning
confidence: 99%
“…Furthermore, linear peptides based on the sequence of uPA lack potency and have poor pharmacological properties and stability due to susceptibility to exoprotease degradation in the plasma [ 153 ]; screening for small-molecule inhibitors is inefficient due to a lack of detailed structural information on the interactions of uPAR with its binding partners such as integrins [ 154 – 156 ]. Some uPAR-targeted small-molecule inhibitors are hydrophobic and have limited bioavailability [ 123 , 125 , 157 ]; and due to the large surface area at the protein–protein interface, the development of small molecules specifically targeting this flexible hydrophobic cavity in uPAR also represent a challenging task [ 129 , 158 ]. Similarly, ligand-targeted toxins must overcome many barriers before they reach human clinical trials, including determining the appropriate dosing strategy and sequence of administration, increasing the potency and reducing the immunogenicity of the toxin [ 159 , 160 ].…”
Section: Targeting Upar For Antitumour Therapymentioning
confidence: 99%
“…Small molecules inhibiting with high affinity uPAR binding to uPA were constructed. They make uPAR unable to bind uPA, modifying its conformation [145,146]. Using a biophysical approach, molecular docking and extensive explicit-solvent molecular dynamics simulations of uPAR bound to uPA, Xu, D. et al demonstrated that the small compound IPR-3011 blocks uPA binding to both open and closed conformations of uPAR [146].…”
Section: Small Molecules Affecting the Upa/upar Systemmentioning
confidence: 99%
“…Building on structural information on the uPA•uPAR interaction, Meroueh et al nevertheless succeeded in developing a small compound (IPR-3011) that inhibited AE147 binding to uPAR with an inhibition constant K i = 2.4 ± 0.3 μM ( Xu et al, 2017 ). Interestingly, that compound inhibited uPA-binding to the open conformation of uPAR wt with a K i = 60 ± 5 μM, while it inhibited uPA-binding to the closed conformation of uPAR H 47 C – N 259 C with a 10-fold improved efficacy K i = 6.6 ± 0.4 μM ( Xu et al, 2021 ).…”
Section: Structure Of Uparmentioning
confidence: 99%